Pengaruh User Interface dan Variasi Produk terhadap Minat Beli Konsumen (Studi Literature) - Saputra, Farhan; Khaira, Nurul; Saputra, Raihan (Jurnal Komunikasi dan Ilmu Sosial, 2023)
Abstract: Research on the Effect of User Interface and Product Variations on Consumer Buying Interest is a literature review article that aims to build hypotheses for further research within the scope of Marketing Management. The method of writing literature review articles is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this literature review article are: 1) User Interface has an effect on Consumer Buying Interest and 2) Product Variation has an effect on Consumer Buying Interest. Apart from these two exogenous variables that affect endogenous variables, there are still many other factors including the variables of Price, Product Quality, Service Quality and Place. Abstrak: Penelitian Pengaruh User Interface dan Variasi Produk terhadap Minat Beli Konsumen merupakan artikel literature review yang bertujuan untuk membangun hipotesis guna penelitian selanjutnya dalam lingkup Manajemen Pemasaran. Metode penulisan artikel literature review yaitu dengan metode library research, yang bersumber dari media online seperti Google Scholar, Mendeley dan media online akademik lainnya. Hasil artikel literature review ini yaitu: 1) User Interface berpengaruh terhadap Minat Beli Konsumen dan 2) Variasi Produk berpengaruh terhadap Minat Beli Konsumen. Selain dari dua variabel exogen ini yang mempengaruhi variabel endogen, masih banyaj faktor lain di antaranya adalah variabel Harga, Kualitas Produk, Kualitas Layanan dan Tempat.